2017
DOI: 10.1242/dev.150656
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 expression in Schwann cells inhibits myelination in vivo and induces influx of macrophages to the nerve

Abstract: Correct myelination is crucial for the function of the peripheral nervous system. Both positive and negative regulators within the axon and Schwann cell function to ensure the correct onset and progression of myelination during both development and following peripheral nerve injury and repair. The Sox2 transcription factor is well known for its roles in the development and maintenance of progenitor and stem cell populations, but has also been proposed as a negative regulator of myelination in Schwann cells. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 64 publications
4
75
0
Order By: Relevance
“…In addition to the phagocytic activity, our data suggest that L‐PGDS may control other processes regulating macrophage number in injured nerves. Previous studies have reported cell proliferation (Mueller et al, ), altered BNB permeability (Liu et al, ; Omura et al, ), chemokines production (DeFrancesco‐Lisowitz et al, ), and more recently, enhanced expression of the transcription factor SOX2 in Schwann cells (Dun et al, ; Roberts et al, ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition to the phagocytic activity, our data suggest that L‐PGDS may control other processes regulating macrophage number in injured nerves. Previous studies have reported cell proliferation (Mueller et al, ), altered BNB permeability (Liu et al, ; Omura et al, ), chemokines production (DeFrancesco‐Lisowitz et al, ), and more recently, enhanced expression of the transcription factor SOX2 in Schwann cells (Dun et al, ; Roberts et al, ).…”
Section: Resultsmentioning
confidence: 96%
“…Lastly, we determined whether altered expression of the transcription factor SOX2 could influence macrophage recruitment. SOX2 is upregulated in Schwann cells soon after injury (Le et al, ) and its overexpression increases macrophage number in uncrushed and crushed nerves (Roberts et al, ). Notably, recent studies have shown that glial SOX2 modulates the signaling between Schwann cells and macrophages to regulate nerve bridge formation after injury (Dun et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the requirement of Sox‐2 to induce collective SC migration is a previously unappreciated role for a stemness factor to control other aspects of progenitor‐cell behavior such as sustained migration. However, the expression of Sox‐2 needs to be tightly regulated, as sustained expression of Sox‐2 following nerve injury appears to be sufficient to maintain SCs in their dedifferentiated state (Roberts et al, ).…”
Section: The Many Roles Of Scs During Nerve Regenerationmentioning
confidence: 99%
“…Repair Schwann cells also express Sox2 (Parrinello et al, ) (Figure c). This transcription factor keeps repair Schwann cells in a proliferative state (Roberts et al, ), and may additionally help to redistribute N‐cadherin downstream of EphB receptors on the Schwann cell surface to allow collective migration and Bungner band formation (Parrinello et al, ). Repair Schwann cells also depend on Stat3 activity to maintain their properties and survive (Benito et al, ) (Figure c).…”
Section: Transcriptional Control Of Peripheral Remyelinationmentioning
confidence: 99%